An Overview of Genes From Cyberlindnera americana, a Symbiont Yeast Isolated From the Gut of the Bark Beetle Dendroctonus rhizophagus (Curculionidae: Scolytinae), Involved in the Detoxification Process Using Genome and Transcriptome Data - Soto-Robles, L. Viridiana; Torres-Banda, Verónica; Rivera-Orduña, Flor N.; Curiel-Quesada, Everardo; Hidalgo-Lara, María Eugenia; Zúñiga, Gerardo (Frontiers in Microbiology, 2019)
Abstract Bark beetles from Dendroctonus genus promote ecological succession and nutrient cycling in coniferous forests. However, they can trigger outbreaks leading to important economic losses in the forest industry. Conifers have evolved resistance mechanisms that can be toxic to insects but at the same time, bark beetles are capable of overcoming tree barriers and colonize these habitats. In this sense, symbiont yeasts present in the gut of bark beetles have been suggested to play a role in the detoxification process of tree defensive chemicals. In the present study, genes related to this process were identified and their response to a terpene highly toxic to bark beetles and their symbionts was analyzed in the Cyberlindnera americana yeast. The genome and transcriptome of C. americana (ChDrAdgY46) isolated from the gut of D. rhizophagus were presented. Genome analysis identified 5 752 protein-coding genes and diverse gene families associated with the detoxification process. The most abundant belonged to the Aldo-Keto Reductase Superfamily, ATP-binding cassette Superfamily, and the Major Facilitator Superfamily transporters. The transcriptome analysis of non-α-pinene stimulated and α-pinene stimulated yeasts showed a significant expression of genes belonging to these families. The activities demonstrated by the genes identified as Aryl-alcohol dehydrogenase and ABC transporter under (+)-α-pinene suggest that they are responsible, that C. americana is a dominant symbiont that resists high amounts of monoterpenes inside the gut of bark beetles.